From theory to practice – assessing translation of physical fitness research in the emergency department through machine learning and natural language processing - Kristin Morrow; Debajyoti Datta; Lindsey Spiegelman; Roy Almog; Kai Zheng; Don Brown; Dan Michael Cooper (Journal of Clinical and Translational Science, 2025)
Abstract